Veterans Affairs databases are accurate for gout-related health care utilization: a validation study - Singh, Jasvinder A (BioMed Central, 2013)
INTRODUCTION: The aim of this study was to assess the accuracy of Veterans Affairs (VA) databases for gout-related health care utilization. METHODS: This retrospective study utilized VA administrative and clinical databases. A random sample of gout patients with visits (outpatient, inpatient or emergent/urgent care) with or without the diagnosis of gout (International Classification of Diseases, ninth revision, common modification ICD-9-CM code of 274.x or 274.xx) at the Birmingham VA hospital was selected. A blinded abstractor performed a review of VA electronic health records for the documentation of gout or gout-related terms (gouty arthritis, tophaceous gout, tophus/tophi, acute gout, chronic gout, podagra, urate stones, urate or uric acid crystals and so on) in the chief complaint, history of present illness or assessment and plan for the visit; this constituted the gold standard for gout-related utilization. The accuracy of database-derived gout-related claims was assessed by calculating sensitivity, specificity, and positive and negative predictive values (PPV and NPV). RESULTS: Of 108 potential visits, 85 outpatient, inpatient or urgent care/emergency room visits to a health care provider (85 patients: 84 men and 1 woman with a mean age of 63 years) and retrievable data from medical records constituted the analyzed dataset. Administrative claims for gout-related utilization with ICD-9 code for gout were accurate with a PPV of 86%, specificity of 95%, sensitivity of 86% and NPV of 95%. CONCLUSIONS: VA databases are accurate for gout-related visits. These findings support their use for studies of health services and outcome studies. It remains to be seen if these findings are generalizable to other settings and databases.